Back Cover: Self‐Powered and Sensitive DNA Detection in a Three‐Dimensional Origami‐Based Biofuel Cell Based on a Porous Pt‐Paper Cathode (Chem. Eur. J. 39/2014). Issue 39 (22nd September 2014) - Wang, Yanhu; Ge, Lei; Ma, Chao; Kong, Qingkun; Yan, Mei; Ge, Shenguang; Yu, Jinghua
<x xml:space="preserve">Abstract</x> A paper‐based self‐powered DNA sensor capable of generating signal output without external power sources was developed by using a biofuel cell. Enzymes catalyzed the oxidation of glucose at the anode, and PtNPs grown on cellulose fibers reduced O2 at the cathode. The all‐solid‐state paper supercapacitor was also integrated for signal amplification. For more information, see the Full Paper by J. Yu et al. on page 12453 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>